2014
DOI: 10.1523/jneurosci.4305-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Is Required for Hair-Cell Differentiation in the Cochlea

Abstract: The development of hair cells in the auditory system can be separated into steps; first, the establishment of progenitors for the sensory epithelium, and second, the differentiation of hair cells. Although the differentiation of hair cells is known to require the expression of basic helix-loop-helix transcription factor, Atoh1, the control of cell proliferation in the region of the developing cochlea that will ultimately become the sensory epithelium and the cues that initiate Atoh1 expression remain obscure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 45 publications
5
106
1
1
Order By: Relevance
“…The increase in IHCs following day 1 CHIR treatment was likely to be caused by directly upregulating Atoh1, a documented Wnt target gene (Kuo et al, 2015;Shi et al, 2010Shi et al, , 2014. At the time of CHIR treatment, Atoh1 expression was already ongoing and Wnt activation boosted it further.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The increase in IHCs following day 1 CHIR treatment was likely to be caused by directly upregulating Atoh1, a documented Wnt target gene (Kuo et al, 2015;Shi et al, 2010Shi et al, , 2014. At the time of CHIR treatment, Atoh1 expression was already ongoing and Wnt activation boosted it further.…”
Section: Discussionmentioning
confidence: 97%
“…Genetic manipulations of the pathway had previously revealed that Wnts function at multiple stages in the embryonic inner ear, beginning with otic induction (Jayasena et al, 2008). Inducible Cre drivers allowed further development of the cochlea before β-catenin was knocked out or overexpressed (Shi et al, 2014). However, it is challenging to correlate phenotypic changes in the OC with specific Wnt ligands or their immediate target genes due to inherent delays between induction, Cre recombination and β-catenin turnover.…”
Section: Discussionmentioning
confidence: 99%
“…ATOH1 must be activated by the canonical WNT effector β-catenin at the appropriate time for hair cell differentiation to proceed [108][109][110] . WNT ligands are thought to be secreted from cells that are outside the sensory epithelium 111 , and their production may cease in the adult ear.…”
Section: Atoh1-dependent Hair Cell Productionmentioning
confidence: 99%
“…Conversely, inhibition of this signaling suppresses proliferation and causes a dramatic decrease in hair cell numbers [68,71]. Therefore, multiple recent studies have focused on regulating the Wnt pathway as a potential target for treating hearing loss [7,[71][72][73][74][75][76][77][78]. A recent study examined the role of epigenetic regulation in colorectal tumorigenesis and found that LSD1 activates the Wnt/β-catenin signaling pathway by downregulating a negative regulator of the pathway, Dickkopf-1 [79].…”
Section: Discussionmentioning
confidence: 99%